Radicicol Confers Mid-Schizont Arrest by Inhibiting Mitochondrial Replication in Plasmodium falciparum - Chalapareddy, Sureshkumar (American Society for Microbiology, 2014)
Radicicol, an antifungal antibiotic, was previously identified as a compound having antimalarial activity. However, its mechanism of action in Plasmodium falciparum was not elucidated. While characterizing its antimalarial function, we observed that radicicol manifested two distinct developmental defects in cultured P. falciparum in a concentration-dependent manner. At a low concentration of radicicol, a significant percentage of drug-treated parasites were arrested at the schizont stage, while at a higher concentration, the parasites were unable to multiply from schizont to ring. Also, the newly formed rings and trophozoites were extremely delayed in development, eventually leading to cell death. We intended to characterize the potential molecular target of radicicol at its sublethal doses. Our results demonstrated that radicicol specifically impaired mitochondrial replication. This decrement was associated with a severalfold increment of the topoisomerase VIB transcript as well as protein in treated cells over that of untreated parasites. Topoisomerase VIB was found to be localized in the organelle fraction. Our docking study revealed that radicicol fits into the Bergerat fold of Pf topoisomerase VIB present in its ATPase domain. Altogether, these data allow us to conclude that P. falciparum topoisomerase VIB might be one of the targets of radicicol causing inhibition of mitochondrial replication. Hence, radicicol can be suitably employed to explore the mitochondrial physiology of malaria parasites.